Hygrocybe nanfengmianensis (Hygrophoraceae, Agaricales), a new species of subsect. Macrosporae from Jiangxi Nanfengmian National Nature Reserve - Guo, Wen-Tao; Liao, Li-Yu; Zhou, Fan; Liao, Xu-Qing; Jiang, Gui-Lan; Yuan, Lin; Hu, Dian-Ming (Phytotaxa, 2025)
Hygrocybe species are a group of brightly colored mushrooms widely distributed across the world, and they represent the most species-rich genus within Hygrophoraceae. In this study, Hygrocybe nanfengmianensis, a new species in subg. Hygrocybe sect. Hygrocybe subsect. Macrosporae, from Jiangxi Nanfengmian National Nature Reserve is described. Hygrocybe nanfengmianensis is characterized by a yellow to orange pileus, pale yellow to yellow lamellae, clavate basidia (30–39 × 8–10 µm), 2 or 4 sterigmata, and possesses clamp connections at the base. Phylogenetic analysis of the species was performed using the ITS and the LSU sequence data. A full description, illustrations, and phylogenetic analysis results of the new species are provided.